(untitled) (Global Journal of Medical Research, 2013)
Atherosclerosis(AS) is one of the most common disease sleading tosevere clinical complications. Atherosclerosis forms pockets of fat and lipid deposit sunder the mucous tunic of blood vessels, which cause progressive vasoconstriction until total luminal blockage occurs. 1Many "Civilization diseases" such as coronary artery disease (CAD), arterial hypertension (AH), diabetes mellitus (DM), psoriasis, gout, and such conditions as hyper lipidemia, hyperglycemia, dyslipidemia, hyperinsulinemia, hypercortisolemia, hyperuricemia, and microalbuminuria are connected with AS development. In these regards, the problem of developing a proven clinical solution for this prevalent disease process is a socially significant one.1,2 During the last 20 years, ASmorbidity has been globally increasing.2,3 Mortality from AS complications, which account for 75-85% of general mortalityinwhole,4 is simultaneously increasing.Thus AS is one of the global problems of conventional medicine.